Public Funding and the “Untamed Wilderness” of Victorian Studies - Wyland, Russell (Romanticism and Victorianism on the Net, 2009)
AbstractVictorian studies emerged, like many interdisciplinary fields, during the 1950s and 1960s. While scholars today accept the validity of interdisciplinary work, it was not always so, and early issues of Victorian Studies and the Victorian Periodicals Newsletter reflect both scholars’ excitement over the prospect of interdisciplinary work and their hesitation in the face of an “untamed wilderness.” The same forces that gave rise to Victorian studies had their equivalent on Capitol Hill with passage of the National Foundation on the Arts and Humanities Act of 1965. This essay explores the relationship between the emerging field of Victorian studies and the National Endowment for the Humanities. The debates and methodological discussions that shaped the founding of the field left scholars well positioned to take advantage of opportunities offered by the Endowment. NEH-supported projects such as Walter Houghton’s Wellesley Index shaped Victorian studies in profound ways, and Victorian studies, in turn, helped shape the Endowment.